Acne and Food Relation: A Naturopathic Perspective - Dias Rima Sutiono; Ibdati Malika; Samirah -; Nadita Putri Almira; Sheila Lestari (PT. Kalbe Farma Tbk., 2020)
Acne is a result of internal imbalance which appears in the form of inflammation, caused by the accummulation of oil, dirt and bacteria under the skin. Acne is the most prevalent skin disease and occurs in all ages, with the highest prevalence in adolescence. Naturopathy is the term for using prevention methods, based on the roots of the disease. This article is to review several scientific evidences on the association between acne and food. Thus, might support naturopathic perspective in acne prevention.Jerawat merupakan hasil ketidakseimbangan internal tubuh yang timbul dalam bentuk peradangan disebabkan oleh tumpukan minyak, kotoran, dan bakteri di bawah kulit. Jerawat merupakan penyakit kulit yang paling umum dan dapat menyerang segala usia,terutama remaja. Naturopati adalah istilah untuk penggunaan metode pencegahan penyakit berdasarkan akar penyebab. Artikel ini akan meninjau beberapa bukti ilmiah hubungan antara jerawat dan makanan. Hal ini dapat mendukung perspektif naturopati untuk mencegah jerawat.